Goat production systems in north Moroccan woodlands: forage production and use of silvopastoral resources - Chebli Y.; Chentouf M.; Hornick J.L.; Cabaraux J.F. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
In northern Morocco, goats feed partly or totally in the woodlands. These forest rangelands currently undergo a huge pressure, related to climate changes and anthropic pressure. This study aimed to evaluate the pastoral potential of these woodlands and to investigate their use. We selected two forest rangelands (Beni Arouss and Derdara) where goat farming has been the dominant activity for decades. To estimate forage production (biomass), we used the method of the reference module. In the same period, interviews were carried out with goat herders. An average of ninety-six plant species was counted in each rangeland. The pastoral shrubs, mainly Arbustus unedo, Cistus crispus, Cistus monspeliensis, Erica arborea, Lavandula stoechas and Pistacia lentiscus, were the main species eaten by goats. For biomass, significant differences were noted according to season and sampling site, with a maximum forage production in spring of 3143 kg DM per hectare and 2905 kg DM per hectare, observed respectively in Beni Arouss and in Derdara. Furthermore, we identified degraded areas dominated by annual species together with species of low pastoral interest and thorny plants. During drought season, when the pastoral offer is limited, pruning of trees is performed during grazing. Due to climate changes and overgrazing, we expect that availability and quality of woodlands used for grazing will continue to decrease over the next decades. The reasonable use of pastures, including a reduction in grazing pressure, should be developed to ensure their sustainability.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)